Thermal inactivation of Escherichia coli O157:H7 and Escherichia coli isolated from morcilla as affected by composition of the product - Oteiza, Juan Martín (2003)
Morcilla is a link sausage quite similar to black pudding, consisting of an inert casing stuffed with a mixture of beef blood, fat, and seasonings. Thirty samples of morcilla showed total microbial counts (6.3×103–2.1×108 Cfu/g ), molds and yeasts (8.9×101–6.3×104 Cfu/g), sulfite-reducing microorganism (2.0×101–2.1×102MPN/g); total coliforms (1.4×101–1.1×103 MPN/g); fecal coliforms (7.0–1.5×102MPN/g); Enterobactereaceae (1.6×102–5.0×105 Cfu/g). S. aureus and B. cereus were not detected. E. coli was detected in 76.6% of the samples analyzed. The thermal resistance (D and z-values) of Escherichia coli O157:H7 and E. coli isolated from morcilla were determined in nutrient broth and in a heating menstruun prepared with ground morcilla (discarding the casing) and added fat or starch. Higher fat and starch levels resulted in higher D-values (min) at 54, 58 and 62 °C for both strains. The z-values (°C) for isolated E. coli in nutrient broth (M1), ground morcilla (M2), M2+10% fat (M3), M2+20% fat (M4), M2+10% starch (M5), and M2+20% starch (M6) were 7.9, 7.8, 10.5, 10.4, 10.3, and 10.4, respectively, and for E. coli O157:H7 were 7.8, 7.4, 9.8, 10.2, 10.3, and 10.7. The composition of product affected heat lethality of the two strains of E. coli.